Sense of community identity and political participation in UNMSM students - Espinoza Quiroz, John Omar (2020)
The purpose of this study was to deepen the subjective experience of a group of members of some of the UNMSM student centers, regarding their political participation in the academic term 2019-II, during the social conflict caused by the construction of a bypass on Venezuela avenue, in the center of Lima city, in October 2019. The interviews were transcribed and analyzed using the Atlas.ti computer program. From a qualitative approach and a phenomenological design, the testimonies derived in five categories and the representative ones were contrasted with the sense of community identity, empowerment, and political participation. It was found that the students consider it relevant to have personal support and feel personal contentment for the learning acquired in coexistence with their university community, which they express during their participation in academic, political and interpersonal relations fields. This practice is associated to individual and organizational empowerment, which links to institutionalized political participation. It is concluded that political participation is transversal to university life and, in this context, student participation in the university is always considered as political.